Bovine alpha-lactalbumin assemblies with capsaicin: Formation, interactions, loading and physiochemical characterization. (1st August 2021) - Romano, Alon; Lajterer, Carolina; Shpigelman, Avi; Lesmes, Uri
Highlights: Native and decalcified alpha lactalbumin bind capsaicin in a cleft via hydrogen bonds or hydrophobic interactions. Protein decalcification decreases affinity (K b ) and binding sites ( n ) for capsaicin. Alpha lactalbumin-capsaicin particulates exhibit a maximum encapsulation efficiency of 47%. pH is a key factor affecting particle formation, encapsulation efficiency and particle size distribution. Abstract: Numerous human conditions can benefit from diets rich in proteins and bioactives, such as capsaicin (CAP), yet their effective delivery is a sensorial, scientific and technological challenge. This study hypothesized that CAP can form various complexes with native bovine alpha-lactalbumin (holo-ALA) and decalcified-ALA (apo-ALA). Calorimetric and spectroscopic techniques reveals ALA-CAP molecular complexation is spontaneous, exothermic and accompanied by various conformational changes. ITC shows the interaction stoichiometry ( n ) and binding constant (K b ) for holo-ALA to be 0.87 ± 0.03, 1.54 ± 0.23 × 10 5 M −1 and for apo-ALA to be 0.64 ± 0.09, 9.41 ± 2.16 × 10 4 M −1 . Molecular docking further elucidates that hydrogen bonds govern CAP binding to holo-ALA while hydrophobic interactions dominate binding to apo-ALA in a structural cleft. Finally, this work shows these interactions along with controlled aggregation can be utilized to form CAP-loaded colloids with encapsulation efficiency of 47.1 ± 1.0%. Thus, this study shows great promise in the prospective use of ALA as an edible delivery vehicle for CAP.